DETERMINE THE WATER QUALITY USING MACROPHYTE INDEX - BATVIAN (NIM: 25314730), KAROLINA
Cisanti Lake as a part of upstream Citarum River has a roles as the sources of main water, tourism, irrigation and fisheries. Therefore, it is important to monitor the water quality of Situ Cisanti. Water quality of Cisanti Lake is being eutrophic and silting up at inlet area. The aims of this study are, to a assessment of water quality using bioindicator macrophytes, which includes diversity of macrophytes using the index Shannon Wiener (H), PI (Pollution Index) and ESMI (Ecological State macrophyte Index) as well as showing the importance of a plant species that have a role in the community using the important value index (IVI). The research was conducted on January-May 2016. The data were rainy season data. Water sampling was conducted at seven sampling points using grab sampling technique. Sampling macrophyte sampling includes five stations that constitute the littoral zone. Water quality of Cisanti Lake comprehensively was fair until unpolluted based on interpretation of index Shannon Wiener (H), PI (Pollution Index) and ESMI (Ecological State macrophyte Index). The average value of all water parameters which above the quality standard of water class II based on PP No. 82/2001 were TSS (station 4), COD (station 4 and station 5), phosphate (station 1, 2, 3, 4, and 5). There was found 26 species of macrophytes which include four types of life: Floating, Emergent, Submerged and Rooted-floating. Abundance species Eichornia crasipess, Paspalum vaginatum, Aternanthera philoxeroides, and Myriophillum aquaticum, aquaticum spread a through spreading all the stations in the littoral zone (station 1, 2, 3, 4, and 5). From the calculation index, an important value obtained four types of macrophytes that have roles and thorough distribution in the littoral zone. Validation result between Shannon Wiener index and pollution index showed strong enough correlation with the value -0,450 so as between pollution index and ESMI with value -0,459. Very weak correlation with the value of -0.064 and 0.083 is the correlation of the pollution index and ESMI with INP. Shannon-Wiener index with IVI showed a weak correlation with the value of -0.202. And the Shannon-Wiener index with Esmi show a very strong correlation with the value of 0.935. Correlation values suggest a link between environmental factors chemical physics with the abundance and diversity of macrophytes. So macrophytes can be used as an a bioindicator to determine of water quality.